PEMANFAATAN TEKNOLOGI SIG UNTUK PEMETAAN TINGKAT ANCAMAN LONGSOR DI KECAMATAN KEJAJAR, WONOSOBO - Nugraha, Satya Budi; Sidiq, Wahid Akhsin Budi Nur; Benardi, Andi Irwan (Universitas Negeri Semarang, 2015)
Kejajar District of Wonosobo Regency was one of region in Central Java Province which has landslide risk.Mountainous topographical factor, steep slope in some area, high rainfall, and low-density of vegetation wereaffected factors of high risk of landslide hazard in that region. This research aimed to determine thedistribution of landslide hazard in Kejajar. Geography Information System (GIS) technology could be used tosupport in mapping of landslide hazardous area in Kejajar District. Through overlay method of someparameter maps, it was hoped that could give imagery of landslide hazard level in study location. Hence,based on information of the map, could be analyzed to give supporting idea in term of landslide management.Based on resulted map of landslide hazard area, there were 4 (four) classification levels. Low level oflandslide hazard were in Sigendeng and Tambi Village. Medium level of landslide hazard were in KreoVillage. High level of landslide hazard was the largest area distribution, included Kejajar, Bantu, Sembungan,Serang, Parikesit, Patakbanteng, Dieng, and Igirmanak Village. While, the very high level of landslide hazardwas in Campursari, Sikunang, Tieng, and Surenggede Village.